Big Data Analytics for Corporate Financial Decision-Making: Evidence from ASEAN Capital Markets - Gogor Christmass Setyawan; Rina Farah; Rashid Rahman; Ii Sopiandi (Journal Markcount Finance, 2025)
The increasing availability and complexity of big data have revolutionized decision-making in various sectors, including corporate finance. In the context of ASEAN capital markets, companies are facing pressure to adopt data-driven strategies to enhance their financial decision-making processes. Big data analytics offers the potential to improve the accuracy of predictions, optimize investment strategies, and manage risks more effectively. This study aims to explore the impact of big data analytics on corporate financial decision-making in ASEAN capital markets, focusing on how organizations utilize data-driven insights to enhance decision-making efficiency and profitability. The research employs a mixed-methods approach, combining quantitative analysis of financial data from publicly listed companies in ASEAN with qualitative interviews from financial executives. The results indicate a positive relationship between big data analytics adoption and improved financial decision-making, particularly in areas of market forecasting, risk management, and asset allocation. Companies that have integrated big data analytics into their financial strategies report better performance in terms of profitability and shareholder value. The study concludes that big data analytics can significantly enhance corporate financial decision-making in ASEAN markets, offering a competitive edge in a rapidly evolving global economy.